1998
DOI: 10.1038/sj.bjp.0702166
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of neuromuscular blocking drugs with recombinant human m1–m5 muscarinic receptors expressed in Chinese hamster ovary cells

Abstract: 1 Neuromuscular blocking drugs (NMBD's) are known to produce cardiovascular side e ects manifesting as brady/tachycardias. In this study we have examined the interaction of a range of steroidal NMBD's with recombinant human m1 ± m5 muscarinic receptors expressed in Chinese hamster ovary cells. Our main hypothesis is that NMBD's may interact with m2 (cardiac) muscarinic receptors. 2 All binding studies were performed with cell membranes prepared from CHO m1 ± m5 cells in 1 ml volumes of 20 mM HEPES, 1 mM MgCl 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 43 publications
1
13
2
Order By: Relevance
“…We found that in M 2 /M 4 double-KO mice, the overall effect of oxotremorine-M was to increase glycinergic sIPSCs. Our observation that the M 3 subtype-preferring mAChR antagonist 4-DAMP (Cembala et al, 1998;Moriya et al, 1999;Zhang et al, 2005) abolished the potentiating effect of oxotremorine-M on sIPSCs in M 2 /M 4 double-KO mice provides further support for our conclusion that the M 3 subtype contributes to the potentiation of spinal glycine release. In M 2 /M 4 double-KO mice, oxotremorine-M significantly increased the frequency of mIPSCs, but significantly less than it increased the frequency of sIPSCs.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…We found that in M 2 /M 4 double-KO mice, the overall effect of oxotremorine-M was to increase glycinergic sIPSCs. Our observation that the M 3 subtype-preferring mAChR antagonist 4-DAMP (Cembala et al, 1998;Moriya et al, 1999;Zhang et al, 2005) abolished the potentiating effect of oxotremorine-M on sIPSCs in M 2 /M 4 double-KO mice provides further support for our conclusion that the M 3 subtype contributes to the potentiation of spinal glycine release. In M 2 /M 4 double-KO mice, oxotremorine-M significantly increased the frequency of mIPSCs, but significantly less than it increased the frequency of sIPSCs.…”
Section: Discussionsupporting
confidence: 74%
“…To confirm the role of the M 3 subtype in the potentiating effect of oxotremorine-M on synaptic glycine release in M 2 /M 4 double-KO mice, we further tested the effect of 5 M oxotremorine-M on glycinergic sIPSCs in the presence of 50 nM 4-DAMP, an M 3 subtype-preferring mAChR antagonist (Cembala et al, 1998;Moriya et al, 1999;Zhang et al, 2005). The potentiating effect of 5 M oxotremorine-M on sIPSCs was completely blocked by subsequent application of 50 nM 4-DAMP in all seven neurons examined (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In untreated cells, cAMP accumulation was significantly reduced by ACh (100 µ M ), and this reduction was abrogated by the M2R antagonist gallamine (10 µ M ). The agent was applied in a concentration selective for M2R over M3R [28]. In poly I:C-treated cells, cAMP accumulation was to a lesser extent attenuated by ACh, and this attenuation was also abrogated by gallamine.…”
Section: Resultsmentioning
confidence: 99%
“…The responses to ACh, histamine, and LTD 4 in untreated and poly I:C-treated cells were completely blocked by the M3R antagonist 4- DAMP (1 µ M ), the H1R antagonist mepyramine (10 µ M ), and the CysLT1R antagonist MK571 (1 µ M ), respectively. 4-DAMP was applied in a concentration selective for M3R over M2R [28]. Complete inhibition of ACh-mediated calcium responses by 4-DAMP in untreated and poly I:C-treated cells implies that basal and upregulated M3R is functional.…”
Section: Resultsmentioning
confidence: 99%
“…[6] For example, the M 5 mAChR is required for cholinergic dilation of central blood arteries and arterioles. For the pharmacological characterization of this binding site, receptor binding experiments with hM 5 stably expressed in CHO cells were for example, phosphate buffer, [19][20][21] Tris-HCl buffer, [22] Krebs-Henseleit buffer, [23] and HEPES buffer, [24][25][26][27] and beyond the incubation time (1-5 h) and temperature (20-37 C). Exposure to organophosphorus compounds has been associated with down-regulation of M 5 AChR related genes.…”
Section: Introductionmentioning
confidence: 99%